Determination of the effect of stress induced by the influence of a predator (Felis silvestris, sub species catus - domestic cat) on the cardiac tissue, brain and cells of the immune system in male species of Rattus novergicus var. Sprague dawley. - Jackeline Zaida Cusirramos Chahua (2019)
The effects of stress on the levels of TGO (Glutamic Oxalacetic Transaminase), leukocyte formula and histological changes in brain and heart of Rattus novergicus variety Sprague Dawley variety were evaluated. The experimental evaluation was carried out in the Laboratory of Animal Physiology of the Academic Department of Biology of the UNSA-Arequipa, during the months of November 2015 to January 2016. 24 Rattus novergicus Sprague Dawley variety assigned in four groups were used: T1 (control group , away from any stimulus that disturbs them), T2 (presence of predators for 20 min./day/day cycle), T3 (presence of predators for 20 min./day / night cycle), T4 (presence of predators for 20 min ./every 7 days / day cycle), for 4 weeks. It was shown that stress causes a statistically significant increase in blood TGO levels in rats, compared to baseline levels, but there is no significant difference between treatments.It was shown that stress affects the basal amounts of the leukocyte formula, finding a statistically significant increase in the amount of circulating monocytes, an increase in averages (although not statistically significant) of circulating Eosinophils, a decrease in averages (although not statistically significant) of Lymphocytes, a statistically significant decrease in the amount of Banded Neutrophils; all these levels in averages with limit values in T3. The amount of Basophils remained indifferent to the effect of stress. The number of Segmented Neutrophils showed a decrease in averages (although not statistically significant) in T4. Stress was shown to cause damage to nervous (edema and vascular congestion) and cardiac (vascular congestion) tissues. Brain swelling was more severe in T3 and T4, while damage to cardiac tissue was similar in treatments T2, T3 and T4.